Comparative study on reproductive biology of Rasbora caudimaculata from the Teluk Petai and Tanjung Kudu Lakes, Kampar Regency, Riau Province - Yofi Kontesa; Windarti Windarti; Ridwan Manda Putra (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2021)
Abstract Rasbora caudimaculata is a type of freshwater fish that commonly inhabit the Teluk Petai Lake and Tanjung Kudu Lake, Kampar Regency, Riau Province. This study aims to understand the reproductive biology of R. caudimaculata. The fish was sampled 4 times, once/week,from November–December 2020. Parameters measured were sexsual characteristics, sex ratio, gonad maturity level, gonad somatic indeks (GSI), fecundity and egg diameter. Results shown that there were 57 fishes from theTeluk Petai Lake and 70 fishes were collected from the Tanjung Kudu Lake. Sex ratio of the fish from the Teluk Petai Lake was 1:2, Gonado Somatic Indeks (GSI) was range from0.00-10.62%,the level of gonad maturity was ranged fromII-V, the average fecundity was1,655-2,677 eggs/fishand egg diameter was 0.55-0.84 mm, while the Tanjung Kudu Lake is fishes, the sex ratio was 1:2, Gonado Somatic Indeks (GSI) 0.18-12.12%,the level of gonad maturity was I-V, the fecundity was 818-2,479 eggs/fishand egg diameter ranged from 0.53-0.86 mm. This fish is partial spawner.Keywords: Sex Ratio, GSI, maturity level, Fecundity, partial spawner